Invitation to Discipleship: Educating for Virtue in Catholic Classrooms - Manning, Patrick R (Lumen et Vita, 2012)
Focus on the virtues has enjoyed a recent resurgence in the field of ethics and has even influenced scholars in religious education. This influence carries positive implications for Catholic education that merit further development. In this paper, the author gleans insights from studies in virtue ethics that may be beneficially applied to Christian formation in the classroom context. The paper begins with a discussion of the relevance of the virtues to the aims of Catholic education before going on to explain how virtues are developed generally and, more specifically, how they can be developed in Catholic classrooms.